Effects of Developing a Heart Catheterization Appointment Service for Patients with Coronary Artery Disease via Electronic Referral System (E-refer) Using Lean Principles - Saeheng, Kanchana; charoensin, chantana; Srichai, Rachanee (Princess of Naradhiwas University Journal, 2025)
Naradhiwas Rajanagarindra Heart Center, Songklanagarind Hospital, is a unit that receives referrals of patients with coronary artery disease for diagnostic angiography and coronary angioplasty procedures. The average waiting time for procedures appointment was 284 minutes, impacting patient’s access to service. This research aimed to study and evaluate the efficiency of providing diagnostic angiography and coronary angioplasty appointment services through an electronic referral system (E-refer) based on lean principles. It was a retrospective quantitative study, collecting data from the electronic registry and medical records of patients referred for procedures between August 2021 and January 2024, divided into groups before and after the implementation of lean principles, with 95 cases in each group. Data were analyzed using descriptive statistics. The results found that after the service was developed, the average duration of all activities decreased from 284 minutes to 17 minutes per case. The service efficiency increased from 8.10% to 47.05%, significantly reducing patient waiting times. In conclusion, the development of the electronic referral system using lean principles can enhance service efficiency and reduce patient waiting times.